Efecto de soluciones nutritivas en 2 variedades de lechuga (Lactuca sativa) sembrada en condiciones hidropónicas en la zona de Santo Domingo de los Tsáchilas. - Llanten Chicaiza, Santiago David (2017)
Taking into account the different soil problems either nutrient deficiencies in the soil caused by excessive exploitation or indiscriminate use of pesticides and contaminants in the soil, in this study the objective was to measure the effect of nutrient solutions on 2 varieties of lettuce (Lactuca sativa) sown in hydroponic conditions in the area of Santo Domingo of the Tsáchilas. For this, seedlings were obtained in germinating trays of two varieties, the transplant was performed at 25 days and plants were placed in the hydroponic system NFT. A completely randomized design was used (DCA), with factorial arrangement of 2 varieties and 4 treatments, To analyze the means was used the test Minimum Significant Difference (DMS), the treatments were: Nutritive solution A (Potassium nitrate 545 g. Folic acid 100 cc. Magnesium sulfate 220 g. Micronutrient fertilizers 12 g. Iron chelate 12.5 g. Boric acid 3 g. Calcium nitrate 700 g. Biostimulant 2 g). Nutritive solution B (Potassium nitrate 570 g. Folic acid 100 cc. Magnesium sulfate 230 g. Micronutrient fertilizers 15 g. Iron chelate 12.5 g. Boric acid 3.5 g. Calcium nitrate 700 g. Biostimulant 3 g). Nutritive solution C (Potassium nitrate 585 g. Folic acid 100 cc. Magnesium sulfate 240 g. Micronutrient fertilizers 17 g. Iron chelate 12.5 g. Boric acid 4 g. Calcium nitrate 700 g. Biostimulant 4 g). Nutritive solution D Hydrocomplex (Ammoniacal Nitrogen 7%. Assimilated phosphorus 11%. Water soluble potassium 18%. Magnesium 2.7%. Sulphur 8%. Boron 0.015%. Iron 0.20%. Manganese 0.02%. Zinc 0.02%). The variety of lettuce Gentilina reached better results at the time of measuring the variables presenting a yield 458 g, more than the variety Salad Bowl. Meanwhile the nutritive solution A, I present the best performance with a difference of 270 g, more than the other nutritional solutions. Keywords: Nutrient Film Technique, Nutritive solutions.